ANALYSIS OF STUDENTS’ ABILITY AND DIFFICULTIES IN WRITING DESCRIPTIVE TEXT - Nazly Salsa Billa; Jamiluddin Jamiluddin; Ferry Rita (e-Journal of ELTS (English Language Teaching Society), 2021)
This research aimed to identification and analysis students’ ability and difficulties in writing descriptive text. This research used qualitative descriptive methods. The research subject are X grade students of Madrasah Aliyah Negeri 1 Palu. The research took 20 students as sample. This research used interview and test to collect the data. The result of this research shows the students’ ability, the students’ difficulty in writing descriptive text and the factors students’ difficulties in writing descriptive texts. The difficulties are difficulties in generic structure, difficulties in grammar, and difficulties in mechanic, while the factors that cause the students’ difficulties in writing descriptive text are lack of proficiency in the text production skills, and lack of interest in learning English